2023
DOI: 10.3389/fcimb.2023.1322537
|View full text |Cite
|
Sign up to set email alerts
|

Causal effect of gut microbiota on Gastroduodenal ulcer: a two-sample Mendelian randomization study

Jing Zhang,
Yingqiu Hu,
Lidong Wu
et al.

Abstract: BackgroundGastroduodenal ulcers are associated with Helicobacter pylori infection and the use of nonsteroidal anti-inflammatory drugs (NSAIDs). However, the causal relationship between gastroduodenal ulcers and gut microbiota, especially specific gut microbiota, remains unclear.MethodsWe conducted an analysis of published data on the gut microbiota and Gastroduodenal ulcer using genome-wide association studies (GWAS). Two-sample Mendelian randomization (MR) analysis was performed to determine the causal relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Specifically, we found that in APC min/+ mice with subchronic exposure to MC-LR, the abundance of Marvinbryantia, Gordonibacter and Family_XIII_AD3011_group was increased, while that of Faecalibaculum, Lachnoclostridium, Bifidobacterium and Turicibacter was significantly decreased. Marvinbryantia was reported to be positively correlated with the risk of gastroduodenal ulcers [56]. Gordonibacter was increased in Western-style-diet-induced mice, which contributed to metabolic-associated fatty liver disease [57].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that in APC min/+ mice with subchronic exposure to MC-LR, the abundance of Marvinbryantia, Gordonibacter and Family_XIII_AD3011_group was increased, while that of Faecalibaculum, Lachnoclostridium, Bifidobacterium and Turicibacter was significantly decreased. Marvinbryantia was reported to be positively correlated with the risk of gastroduodenal ulcers [56]. Gordonibacter was increased in Western-style-diet-induced mice, which contributed to metabolic-associated fatty liver disease [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that delayed neurocognitive recovery was enriched by Anaerofilum compared to the non-delayed neurocognitive recovery group ( 42 ). The study of the relationship between Dorea and insomnia ( 43 ), Lachnospiraceae UCG-010 and chronic kidney disease ( 44 ), Ruminococcus_2 and rheumatoid arthritis ( 45 ), order NB1n and gastroduodenal ulcers ( 46 ) highlight the potential for GM-focused treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The WME approach weighted the causal effect of different genetic variants on traits and then took its median as the final causal effect estimate. Even when 50% of the weight was derived from invalid IVs, it could provide consistent estimates ( Bowden et al, 2016 ; Zhang et al, 2023 ). The WME estimation results are preferred when there is only heterogeneity but no pleiotropy.…”
Section: Methodsmentioning
confidence: 99%